Tension identification method of structural cable based on calibration principle in engineering. (December 2022) - Guo, Liulu; Liu, Hongbo; Chen, Zhihua; Wang, Longxuan; Ma, Hongxu
Abstract: This paper proposes a practical cable tension identification method based on the calibration principle for in-service building cables in engineering. Based on the beam model theory of vibration method and Zui. H theory formula, a general cable force-frequency model is proposed. Then, the tension and frequency of the cable during the construction is calibrated to fit the model parameters. The cable force identification is realized by testing the cable frequency during service. In this paper, the cable force frequency calibration test is carried out on the semi-parallel wire cable and typical pre-stressed structures, and the cable force frequency database is obtained. The tension prediction model is fitted by some data and verified by the rest data. The root mean square error and the goodness of fit are calculated, and the applicability of the method is verified by comparing with the existing method. The cable tension identification method provides a new idea for the cable force identification of in-service cables in engineering.